USER EXPERIENCE ANALYSIS OF THE CANVA APPLICATION USING THE SYSTEM USABILITY SCALE (SUS) METHOD. - Nida’ul Hasanati; Ainun Nashikha (Indragiri Islamic University, 2023)
The Canva Design application has gained popularity among users seeking to design graphics and visual content. However, users face challenges such as difficulty finding features, slow performance, unclear user interface, and functional issues. This research aims to identify and analyze these problems through User Experience and System Usability Scale (SUS) analysis. The findings provide valuable insights to Canva's development team to address weaknesses and improve usability. This research serves as a foundation for enhancing the quality and user-friendliness of the Canva application to meet the evolving needs and expectations of users.